Expression of mRNAs related to connective tissue metabolism in rat hepatic stellate cells and myofibroblasts - Mrkvicová, Alena; Slavkovský, Rastislav; Čermáková, Martina; Bittnerová, Lenka; Hanovcová, Irena; Bolehovská, Radka; Hajzlerová, M; Radilová, Hana; Ruszová, Ema; Kanta, Jiří (Experimental and toxicologic pathology, 2007)
Hepatic stellate cells (HSC) and liver myofibroblasts (MFB) are two cell populations most likely responsible for the synthesis of most connective tissue components in fibrotic liver. They differ in their origin and location, and possibly in patterns of gene expression. Normal and carbon tetrachloride-cirrhotic livers from rats were used to isolate HSC. Liver was perfused with pronase and collagenase solutions, followed by centrifugation of the cell suspension on a density gradient. HSC were quiescent 2 days after plating on plastic but they became activated after another 5 days in culture. When the culture was passaged 5 times, its character changed profoundly as HSC were replaced by MFB. Microarray analysis was used to determine gene expression in quiescent HSC, activated HSC and MFB. The expression of 49 genes coding for connective tissue proteins, proteoglycans, metalloproteinases and their inhibitors, growth factors and cellular markers was determined. The pattern of gene expression changed during HSC activation and there were distinct differences between HSC and MFB. Little difference between normal cells and cells isolated from cirrhotic liver was found.
Keywords: Myocytes, Smooth Muscle; metaloproteasy; Oligonucleotide Array Sequence Analysis; Liver Cirrhosis, Experimental; tkáňové inhibitory metaloproteinas; Reverse Transcriptase Polymerase Chain Reaction; Cells, Cultured; pojivová tkáň; otrava chloridem uhličitým; experimentální cirhóza jater; zvířata; Rats; Financing, Organized; proteoglykany; messenger RNA; Tissue Inhibitor of Metalloproteinases; imunohistochemie; financování organizované; Immunohistochemistry; Metalloproteases; polymerázová řetězová reakce s reverzní transkripcí; extracelulární matrix; Proteoglycans; Carbon Tetrachloride Poisoning; sekvenční analýza hybridizací s uspořádaným souborem oligonukleotidů; kultivované buňky; krysa rodu Rattus; Gene Expression; Liver; Animals; Connective Tissue; Extracellular Matrix; RNA, Messenger; fibroblasty; játra; Fibroblasts; myocyty hladké svaloviny; exprese genu